Comparison between predicted and observed compressibility characteristics of treated soil using precompression and vertical drain - Azhani Zukri, 1976-; Kamarudin Ahmad; Fakulti Kejuruteraan Awam (2010)
Thesis (Sarjana Kejuruteraan (Awam - Geoteknik)) - Universiti Teknologi Malaysia, 2010